Students Barriers in Online Learning of Covid 19 Pandemic for Fifth Grade in English Language Study Program of Sisingamangaraja XII University Tapanuli - Rekolina Siahaan; Holmes Rajagukguk (Institute of Computer Science (IOCS), 2021)
This research aims to explore the problems that have the potential of students' understanding during online learning by Covid 19, the researchers focus on obstacles in the student learning process such as network constraints, no quota and other related matters. Subjects in this study were fifth grade students of English study program. The research is used qualitative with descriptive approach in the process using Observation and Interview methods as the main way to obtain data where the results of this study classify the main problems that arise into 2 parts, namely; 1) There is a delay from the subject in participating in online class activities, 2) the lack of time and ability during the learning process either because they do not have sufficient understanding of the material or there are other activities or work that must be undertaken.